Isolated generalised anhidrosis induced by postganglionic sympathetic skin nerve fibre degeneration: an incomplete Ross syndrome?. Issue 8 (20th March 2008) - Donadio, V; Cortelli, P; Falzone, F; Bugiardini, E; Giuliani, A; Misciali, C; Montagna, P; Calzà, L; Liguori, R
Abstract : Ross syndrome is characterised by tonic pupil, areflexia and anhidrosis, and the underlying lesion affects postganglionic skin sympathetic nerve fibres. We describe a 51-year-old man who had complained of anhidrosis since adolescence, at which time this problem was limited to the lower arms. The thermoregulatory sweating test disclosed generalised anhidrosis (GA) except for two small skin areas that were located in the right palm and left neck. Immunofluorescence analysis disclosed no cholinergic sudomotor fibres around the sweat glands of non-sweating skin areas, which were evident although sparse and deranged in the sweating site. In our patient, GA was induced by degeneration of postganglionic sympathetic skin nerve fibres, as found in Ross syndrome, although his clinical picture was incomplete as it lacked tonic pupil and areflexia. Isolated GA induced by degeneration of postganglionic sympathetic nerve fibers, directly evaluated by skin biopsy, has not previously been described.